Implementasi Kebijakan Pengelolaan Barang Milik Negara pada Pengadilan Agama Lubuk Linggau - Amelia, Amelia; Jefri, Riny (Badan Penelitian dan Pengembangan Daerah Provinsi Sumatera Selatan, 2025)
The research was conducted to study how the implementation of policies regarding the management of state property at the Lubuk Linggau Religious Court. This research uses a qualitative descriptive method that produces descriptive data in the form of written or spoken words and behavior that can be observed by researchers. Data collection using this method is carried out by means of observation, interviews and documentation related to the management of state-owned assets. Data reduction, data presentation, drawing conclusions, verification and validity testing are steps in the data analysis process carried out by researchers. The results of the research explain that the implementation of policies on the management of state assets at the Lubuk Linggau Religious Court has been guided by Government Regulation Number 28 of 2020, but in its implementation it has not run optimally. Several obstacles were found in the implementation of state-owned assets management, including poor coordination and cooperation among employees, state-owned assets management officers who were not yet competent in managing state-owned assets, and changes in the condition of state-owned assets that were not immediately reported.